Loyalitas Suporter di Tengah Fluktuasi Prestasi PSM Makassar (Tinjauan Sosiologi Olahraga) - Kambie, Akhmad Sudirman (Universitas Muhammadiyah Makassar, 2026)
This article examines the loyalty of PSM Makassar supporters amid fluctuations in team performance during the 2025–2026 Indonesian Super League season from a sociology of sport perspective. The central phenomenon analyzed is the absence of collective emotional escalation among supporters despite PSM Makassar experiencing consecutive defeats a situation that, within modern football culture, often triggers conflict and the delegitimization of clubs. From a competitive standpoint, PSM Makassar exhibits recurring patterns of performance instability, both across seasons and within a single competition season, indicating that the championship achieved in the 2022–2023 season has not yet been fully institutionalized as sustainable success. Nevertheless, these fluctuations have not significantly eroded the club’s social legitimacy among its supporters. This study employs a qualitative approach with a case study design. Data were collected through non-participant observation, visual documentation, and analysis of media archives and online news coverage. The data were analyzed thematically using source triangulation. The findings indicate that PSM Makassar supporters interpret defeat as part of the natural rhythm of competition rather than as a collective moral failure. Through the lenses of liquid modernity and burnout society, supporter loyalty is understood as a social mechanism that restrains the pressure of the sports industry’s logic, which emphasizes instant results. Loyalty is institutionalized through symbolic practices, post-match rituals, and the local cultural value of siri’ na pacce, which strengthens solidarity and the regulation of collective emotions.